On the surface scratch and thermal fatigue damage of wheel material under different braking speed conditions. (September 2017) - He, C.G.; Chen, Y.Z.; Huang, Y.B.; Liu, Q.Y.; Zhu, M.H.; Wang, W.J.
Abstract: The surface scratch and thermal fatigue damage of wheel and rail materials are imperative problems affecting safety and stable operation of railway transportation. This study is to explore the surface scratch damage and thermal fatigue cracks for wheel material at different braking speeds. The results indicate that surface scratch morphology presents marked thermal fatigue cracks and plowing damage with an increase in braking speed. The shallow thermal fatigue cracks initiate on wheel roller surface and then propagate parallel with the contact surface at low braking speed. However, serious thermal fatigue cracks tend to branch and propagate toward inner material at high braking speed. The frictional heat makes the yield strength of wheel materials decrease, which aggravates the thermal fatigue damage as braking speed increasing. Graphical abstract: Highlights: The test rig is able to produce scratch that similar to damage on the wheel tread. Braking speed plays a vital role in scratch and thermal fatigue crack of material. In the role of frictional heat, the thermal cracks initiate on wheel surface. Thermal cracks are prone to propagate toward internal material at large braking speed.